2019
DOI: 10.12965/jer.1938174.087
|View full text |Cite
|
Sign up to set email alerts
|

Virtual rehabilitation of upper extremity function and independence for stoke: a meta-analysis

Abstract: We aimed to conduct a systematic literature review with a meta-analysis to investigate whether virtual reality (VR) approaches have beneficial effects on the upper extremity function and independent activities of stroke survivors. Experimental studies published between 2007 and 2017 were searched from two databases (EBSCOhost and PubMed). This study reviewed abstracts and assessed full articles to obtain evidence on qualitative studies. For the meta-analysis, the studies that estimated the standardized mean be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…For people with ABI Saywell [ 61 ] identified a medium and significant effect of VR but with low quality of evidence for independence outcome. For people who had had a stroke two reviews [ 30 , 63 ] identified small and large effects in favour of VR on activities of daily living, but with very low and low quality of evidence. Reported heterogeneity was low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For people with ABI Saywell [ 61 ] identified a medium and significant effect of VR but with low quality of evidence for independence outcome. For people who had had a stroke two reviews [ 30 , 63 ] identified small and large effects in favour of VR on activities of daily living, but with very low and low quality of evidence. Reported heterogeneity was low.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, results offer support in favour of customized VR systems compared to commercially available VR systems (e.g., Nintendo Wii, Microsoft Kinect), especially for upper limb extremity, body function and activity. Bespoke VR systems are more likely to follow rehabilitation principles compared to commercial VR by adjusting to user needs and abilities, supporting feedback, task-specific practice and usage of affected limb, and increasing difficulty [ 10 , 30 , 31 ]. Research using these environments is also more likely to design and conduct usability evaluations with users to select the type of tasks and activities to reach specific rehabilitation goals [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such applications for patient care include the treatment of acute and chronic pain [14,15,16,17,18], specific phobias [19,20], and post-traumatic stress disorder [20,21]. Among several other applications, VR has been successfully used in cognitive and physical rehabilitation after stroke [22,23] and traumatic brain injury [24].…”
Section: Introductionmentioning
confidence: 99%
“…The use of VR technology in rehabilitation derives from research in computational neuroscience involving motor learning mechanisms [10]. VR provides real-time visual feedback for movements, thereby increasing engagement in enjoyable rehabilitation tasks [11].…”
Section: Introductionmentioning
confidence: 99%